2004
DOI: 10.1007/bf02410317
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties and battery discharge characteristics of the Ag+ ion conducting composite electrolyte system (1−x)[0.75AgI: 0.25AgCl]: xFe2O3

Abstract: Abstract. Ion transport and battery discharge characteristic studies are reported for a new Ag + ion conducting two-phase composite electrolyte system (1-x)[0.75AgI: 0.25AgC1]: xFe203, where 0 < x < 0.5 in molar weight fraction. An alternative single-phase host-matrix 'annealed [0.75AgI: 0.25AgC1] mixed system/solid solution' has been used in place of the traditional host, AgI. Submicron size particles (< 1 gm) of Fe203 has been used as second phase dispersoid. The composition 0.8[0.75Agi: 0.25AgC1]: 0.2Fe:O3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This change in mobility (l) and mobile ion concentration (n) well ahead of transition temperature ($135°C) of the host can be attributed as a pre-transition effect [20,[13][14][15][16]. The rapid decrease in value of mobility (l) from region-I to region-II, can be attributed to the structure volume concentration of the host compound in a-like phase, which has resulted into a space narrowing for ion migration as well as blocking effect of dispersoid particles, while abrupt increase of mobile ion concentration (n) from region-I to region-II is due to the fact that the host acquires an entirely new structure a-like phase where a large number of equi-energetic Ag + ions become available for conduction [13][14][15][16]18]. The transference number (t ion ) and ionic drift velocity (v d ) measurement were also carried out on newly synthesized composite system: 0.85[0.75AgI:0.25AgCl]: 0.15CeO 2 using TIC technique.…”
Section: Phase Identification/materials Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…This change in mobility (l) and mobile ion concentration (n) well ahead of transition temperature ($135°C) of the host can be attributed as a pre-transition effect [20,[13][14][15][16]. The rapid decrease in value of mobility (l) from region-I to region-II, can be attributed to the structure volume concentration of the host compound in a-like phase, which has resulted into a space narrowing for ion migration as well as blocking effect of dispersoid particles, while abrupt increase of mobile ion concentration (n) from region-I to region-II is due to the fact that the host acquires an entirely new structure a-like phase where a large number of equi-energetic Ag + ions become available for conduction [13][14][15][16]18]. The transference number (t ion ) and ionic drift velocity (v d ) measurement were also carried out on newly synthesized composite system: 0.85[0.75AgI:0.25AgCl]: 0.15CeO 2 using TIC technique.…”
Section: Phase Identification/materials Characterizationmentioning
confidence: 98%
“…The enhancement of the conductivity in these systems is generally due to creation of double layer space-charge region at the host/ dispersoid interface and the increase in defect concentration in this region. In additions to this, high conducting paths, interconnecting the various space-charge regions are also created, which result in an enhancement of the ionic mobility and/or mobile ion concentration and contribute to the enhancement in the ionic conductivity [13][14][15][16][17][18]. Generally fast Ag + ion conducting two-phase composite electrolyte system was prepared using AgI as a host salt.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that a relatively higher conductivity enhancement could be achieved when AgI is used as a first phase host matrix [16]. In 1994, a new alternative host salt [0.75AgI:0 .25AgCl] has been investigated [17,18], by using this newly synthesized host salt as first phase, several two-phase composite electrolyte systems have been reported recently [19][20][21][22]. These composite electrolyte systems exhibited superior transport properties compared to those of AgI based twophase composite electrolyte systems.…”
Section: Introductionmentioning
confidence: 98%
“…The ionic conductivity of several composite solid electrolytes have been found to depend significantly on the type of insulating second phase particles. Various composite solid electrolytes synthesized using many different types of the insulating second phase such as Al 2 O 3 , SiO 2 , CeO 2 , ZrO 2, Fe 2 O 3 etc [6][7][8][9][10][11] have been reported in the literature. Most composite electrolytes were prepared by solid state reaction technique which involves heating at high temperatures and it show high ionic conductivity at high temperatures.…”
Section: Introductionmentioning
confidence: 99%